Study the Features of 57 Confirmed CRISPR Loci in 38 Strains of Staphylococcus aureus - Zhao, Xihong; Yu, Zhixue; Xu, Zhenbo (Frontiers in Microbiology, 2018)
Staphylococcus aureus is a foodborne pathogen that causes food contamination and food poisoning, which poses great harm to health, agriculture and other hosts. Clustered regularly interspaced short palindromic repeats (CRISPR) are a recently discovered bacterial immune system that resists foreign genes such as phage DNA. This system inhibits the transfer of specific movable genetic elements that match the CRISPR spacer sequences, thereby preventing the spread of drug-resistant genes between pathogens. In this study, 57 CRISPR loci were screened from 38 strains of S. aureus based on the CRISPR database, and bioinformatics tools were used to investigate the structural features and potential functions of S. aureus CRISPR loci. The results showed that most strains contained only one CRISPR locus, a few strains contained multiple loci with sparsely distributed sites. These loci mainly included highly conserved direct repeat sequences and highly variable spacer sequences, as well as polymorphic cas genes. In addition, the analysis of secondary structure of direct repeat RNA showed that all sites can form stable RNA secondary structure. The results of constructing phylogenetic tree based on spacer sequence showed that some strains contained a high degree of phylogenetic relationship, while the differences among other strains in evolutionary processes were quite obvious. Of the 57 CRISPR loci identified, only the cas gene was found near the 4 CRISPR loci.